Functional FLT1 Genetic Variation is a Prognostic Factor for Recurrence in Stage I–III Non–Small-Cell Lung Cancer. Issue 7 (July 2015) - Glubb, Dylan M.; Paré-Brunet, Laia; Jantus-Lewintre, Eloisa; Jiang, Chen; Crona, Daniel; Etheridge, Amy S.; Mirza, Osman; Zhang, Wei; Seiser, Eric L.; Rzyman, Witold; Jassem, Jacek; Auman, Todd; et al.
<x xml:space="preserve">Abstract</x> Background: We propose that single-nucleotide polymorphisms (SNPs) in genes of the vascular endothelial growth factor pathway of angiogenesis will associate with survival in non–small-cell lung cancer (NSCLC) patients. Methods: Fifty-three SNPs in vascular endothelial growth factor-pathway genes were genotyped in 150 European stage I–III NSCLC patients and tested for associations with patient survival. Replication was performed in an independent cohort of 142 European stage I–III patients. Reporter gene assays were used to assess the effects of SNPs on transcriptional activity. Results: In the initial cohort, five SNPs associated (q < 0.05) with relapse-free survival (RFS). The minor alleles of intronic FLT1 SNPs, rs7996030 and rs9582036, associated with reduced RFS (hazard ratio [HR] = 1.67 [95% confidence interval, CI, 1.22–2.29] and HR = 1.51 [95% CI, 1.14–2.01], respectively) and reduced transcriptional activity. The minor alleles of intronic KRAS SNPs, rs12813551 and rs10505980, associated with increased RFS (HR = 0.64 [0.46–0.87] and HR = 0.64 [0.47–0.87], respectively), and the minor allelic variant of rs12813551 also reduced transcriptional activity. Lastly, the minor allele of the intronic KRAS SNP rs10842513 associated with reduced RFS (HR = 1.65 [95% CI, 1.16–2.37]). Analysis of the functional variants suggests they are located in transcriptional enhancer elements. The negative effect of rs9582036 on RFS was confirmed in the replication cohort (HR = 1.69 [0.99–2.89], p = 0.028), and the association was significant in pooled analysis of both cohorts (HR = 1.67 [1.21–2.30], p = 0.0001). Conclusions: The functional FLT1 variant rs9582036 is a prognostic determinant of recurrence in stage I–III NSCLC. Its predictive value should be tested in the adjuvant setting of stage I–III NSCLC.